Effects of cordierite particulate filters on diesel engine exhaust emissions in terms of pollution prevention approaches for better environmental management. (1st September 2021) - Yildiz, Ibrahim; Caliskan, Hakan; Mori, Kazutoshi
Abstract: In this study, a specific diesel fuel is experimentally tested in a 4-cylindered diesel engine with and without a cordierite-based diesel particulate filter (CPF) to show the prevention of emissions by using an after treatment system (ATS). In this context, engine exhaust emissions, total particle concentration (TPC) and soot concentration are investigated. The diesel engine is firstly evaluated with the data directly measured from the engine output (DEO) (without after treatment option), and then the changes in the exhaust emission are examined by using an ATS which is a cordierite-based diesel particulate filter to prevent pollution. In this regard, total particle concentration of DEO option is found to be 6134041.20 1/cm 3 and total particle concentration by using CPF is obtained to be 707.84 1/cm 3 . 99.99% reduction in TPC is achieved thanks to the use of CPF. The soot concentration of DEO option is calculated to be 2.158 mg/m 3 . However, the soot concentration is found to be 0.014 mg/m 3 by using the CPF. The particulate matters are burned at high temperatures after being filtered at the exhaust output thanks to the regeneration process within the CPF after treatment. CO emissions decreased from 0.7489 g/kWh to 0.7273 g/kWh with the CPF utilization, while HC emissions decreased from 0.0965 g/kWh to 0.0900 g/kWh via CPF. However, an increase in CO2 and NOx emissions are observed due to oxidation in the CPF. Highlights: Engine exhaust pollution prevention technology for better environmental management. Effects of cordierite after treatment system on engine exhaust emissions and soot. Comparison of engine emission with and without after treatment system.